PENGARUH BUDAYA ORGANISASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI KERJA SEBAGAI MEDIASI ( Studi Pada AO Transport & Shuttle di Yogyakarta) - Irsyad Darmawan (JURNAL STUDI MANAJEMEN ORGANISASI, 2021)
This study aims to determine: (1) The influence of organizational culture on the performance of AO Transport & Shuttle employees in Yogyakarta, (2) The influence of the work environment on the performance of AO Transport & Shuttle employees in Yogyakarta, (3) The influence of organizational culture on employee performance through work motivation AO Transport & Shuttle employees in Yogyakarta, (4) The influence of the work environment on employee performance through the work motivation of AO Transport & Shuttle employees in Yogyakarta. Sampling used in this study is saturated sampling (census), in which all members of the population are sampled. The number of employees at AO Transport & Shuttle in Yogyakarta is 37 people. This study uses a survey method that is research conducted using a questionnaire as a research tool. Data collection by interview and questionnaire was compiled with a Likert Scale and then calculated using the SPSS method. The results of this study are: (1) Organizational culture directly influences employee performance with a beta coefficient of 0.273 and a significance of 0.022; (2) The work environment has a direct effect on employee performance with a beta coefficient of 0.474 and a significance of 0.000; (3) Organizational culture has no indirect effect on employee performance mediated by work motivation with a total influence of 0.371, and t arithmetic of 0.5187 <2.0345 (t table) with a significance level of 0.05; (4) The work environment has no indirect effect on employee performance mediated by work motivation with a total influence of 0.595, and t count is 1.7824 <2.0345 (t table) with a significance level of 0.05. Keywords: Organizational Culture, Work Environment, Work Motivation, and Employee Performance.